ANALISIS POTENSI PENERIMAAN DAN EFEKTIVITAS PPN ATAS PENYERAHAN KENDARAAN BERMOTOR BEKAS TERHADAP PENERIMAAN PPN (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Malang Utara) - Aprilian, Yudha Alief (Jurnal Mahasiswa Perpajakan, 2014)
This research aims to find how potential of VAT on submission of secondhand motor vehicles, effectiveness of the VAT on submission of secondhand motor vehicles and influence on VAT receipts at KPP Pratama North Malang. First, analysis by calculating the trend equation to determine the earning potential of VAT on Submission of Secondhand Motor Vehicles. Second, Â analysis to calculate the level of effectiveness between 2011 until 2013. Third, analysis to calculate the contribution of VAT on Submission of Secondhand Motor Vehicles to VAT at KPP Pratama North Malang. This research used a descriptive research with a qualitative approach. The technique of data collection in this research is by interview and documentation. The type of interview is semi-structured interview. The results of this research indicated that: First, VAT receipts on submission of secondhand motor vehicles has the potential can be explored. Second, the effectiveness of VAT on Submission of Secondhand Motor Vehicles collection system is quite effective. Third, the contribution of VAT receipt on submission of secondhand motor vehicles to the VAT can be interpreted very less. Based on the results of research, that are controlling and counseling are needed to make correction. Keywords: potential of VAT on submission of secondhand motor vehicles, effectiveness of the VAT on submission of secondhand motor vehicles, the contribution